„Książka nieufności”. O Rosji Czesława Miłosza - Wedemann, Marek (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
The article is a review of an extensive, two-volume collection of Miłosz’s statements entitled Rosja. Widzenia transoceaniczne [Russia: Transoceanic Views]. The reviewer, apart from a standard presentation and evaluation of the published work, attempts to discover a deeper sense of the decision to publish, “here and now”, Miłosz’s statements on Russian issues. The collection, which rounds up previously unknown texts written between 1936 and 2004, makes it possible to understand Miłosz’s writings on Russia as a continuation of Marian Zdziechowski’s essays written between the wars, where uncompromising denunciation of the “Eastern peril” was combined with deep respect and sympathy for a Russia that was not imperial.